Come, sweet death: targeting glycosomal protein import for antitrypanosomal drug development. (December 2018) - Kalel, Vishal C; Mäser, Pascal; Sattler, Michael; Erdmann, Ralf; Popowicz, Grzegorz M
Abstract : Glycosomes evolved as specialized system for glycolysis in trypanosomatids. These organelle rely on protein import to maintain function. A machinery of peroxin (PEX) proteins is responsible for recognition and transport of glycosomal proteins to the organelle. Disruption of PEX-based import system was expected to be a strategy against trypanosomatids. Recently, a proof of this hypothesis has been presented. Here, we review current information about trypanosomatids' glycosomal transport components as targets for new trypanocidal therapies.